2000
DOI: 10.1128/jb.182.24.6975-6982.2000
|View full text |Cite
|
Sign up to set email alerts
|

Mutational Analysis of Conserved Residues in the Putative DNA-Binding Domain of the Response Regulator Spo0A of Bacillus subtilis

Abstract: The Spo0A protein of Bacillus subtilis is a DNA-binding protein that is required for the expression of genes involved in the initiation of sporulation. Spo0A binds directly to and both activates and represses transcription from the promoters of several genes required during the onset of endospore formation. The C-terminal 113 residues are known to contain the DNA-binding activity of Spo0A. Previous studies identified a region of the Cterminal half of Spo0A that is highly conserved among species of endospore-fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 57 publications
1
3
0
Order By: Relevance
“…Perhaps surprisingly, only Glu213, Arg214 and Arg217 make direct contact to the DNA bases, to impart sequence‐specificity on the interaction, and just three of the seven bases (positions 2, 4 and 5) in the canonical ‘0A’ box, 5′‐TGTCGAA‐3′, are contacted directly by these three amino acids. Mutation in Spo0A at Glu213 and Arg214 abolishes DNA‐binding and transcription activation and repression [46,47]. This structure validates the findings that mutation of ‘0A’ boxes at various promoters at positions 4 and 5 that increase Spo0A activity restore the consensus sequence whereas mutations away from the consensus at positions 4 and 5 reduce Spo0A activity [21].…”
Section: Proteomicssupporting
confidence: 78%
“…Perhaps surprisingly, only Glu213, Arg214 and Arg217 make direct contact to the DNA bases, to impart sequence‐specificity on the interaction, and just three of the seven bases (positions 2, 4 and 5) in the canonical ‘0A’ box, 5′‐TGTCGAA‐3′, are contacted directly by these three amino acids. Mutation in Spo0A at Glu213 and Arg214 abolishes DNA‐binding and transcription activation and repression [46,47]. This structure validates the findings that mutation of ‘0A’ boxes at various promoters at positions 4 and 5 that increase Spo0A activity restore the consensus sequence whereas mutations away from the consensus at positions 4 and 5 reduce Spo0A activity [21].…”
Section: Proteomicssupporting
confidence: 78%
“…The R206G/A mutant lost both functions [Hatt et al, 2000]. The mode of evolution for Spo0A has maintained these residues in all species; there could therefore be Spo0A-boosted activities, depending on the type of mutation induced.…”
Section: The Dna Binding Domainmentioning
confidence: 97%
“…The region shown in italics corresponds to the CRII sequence; this area is fundamental in recognising the 0A box [Hatt et al, 2000;Lewis et al, 2000a]; the residues highlighted in bold were identified as being traces for this area of the protein. The functional role of several residues identified in this region have already been studied; residues Y190, R203 and H210 are important in determining the conformational characteristics of the protein and residues E205, R206 and R209 are fundamental in interaction with the target DNA molecule [Zhao et al, 2002].…”
Section: The Dna Binding Domainmentioning
confidence: 99%
“…Mutation in Spo0A at Glu213 and Arg214 abolishes DNA-binding and transcription activation and repression [46,47]. Perhaps surprisingly, only Glu213, Arg214 and Arg217 make direct contact to the DNA bases, to impart sequence-specificity on the interaction, and just three of the seven bases (positions 2, 4 and 5) in the canonical Ô0AÕ box, 5 0 -TGTCGAA-3 0 , are contacted directly by these three amino acids.…”
Section: Dna Recognition By Spo0amentioning
confidence: 99%